ANALYZING MICRO-GRADIENT EFFECTS: A COMPARATIVE RESEARCH ON CO2 EMISSION IN BLACKWATER ECOSYSTEMS - Harper, Claire Elizabeth; Richardson , Thomas Edward (Ayden Journal of Agriculture and Allied Studies, 2024)
With the global human population rapidly approaching eight billion, the imperative to safeguard sensitive ecosystems has never been more critical for the planet's long-term survival. Wetlands, vital components of the Earth's ecological health, encompass approximately 6% of terrestrial land areas worldwide. In the United States alone, they span 274 million acres, constituting a remarkable 14% of the world's wetlands (Reddy & DeLaune, 2008). These ecosystems serve as crucial carbon reservoirs, estimated to store between 350-535 gigatons of carbon (Mitra et al., 2005). However, the looming specter of climate change, characterized by shifting global temperatures and erratic flood-drought cycles, poses an existential threat to wetlands. The potential desiccation of these fragile environments could result in the release of vast quantities of carbon back into the atmosphere. Elevated atmospheric temperatures have already triggered a reduction in surface and groundwater levels due to increased evapotranspiration. Consequently, climate change underscores the pressing need for wetland preservation while propelling innovation to create new wetlands capable of providing equivalent ecosystem services. This study makes a significant contribution by emphasizing the pivotal role wetlands can play in mitigating global climate change. It underscores the intricate relationship between soil moisture, temperature dynamics, and CO2 efflux, thereby enhancing our understanding of wetlands' potential in combating climate change.